An insight into the firing conditions of Chinese blue-and-white porcelain through XANES - Coutinho, ML (2022)
ABSTRACT: Chinese blue-and-white porcelain is found in archaeological excavations worldwide, being significant evidence of global trade routes and cultural exchange. Synchrotron radiation-based techniques have been applied for studying cobalt speciation to establish a correlation between the cobalt and iron oxidation state and local coordination environment in the rich blue shades of Chinese blue-and-white porcelain. However, the relationship between the firing atmosphere conditions and the speciation of cobalt has not been established yet. In this study, underglaze blue models were produced and fired in air or under reducing atmospheres to ascertain the effect of the firing atmosphere in cobalt and iron speciation. The experimental results were compared with data obtained on historical samples of ancient porcelain shards. The microstructure and colour of the produced underglaze blue models were investigated by variable pressure scanning electron microscopy (VP-SEM-EDS), using a hyperspectral imaging camera (Vis-SWIR reflectance spectroscopy) and colorimetry. The formal valence and coordination of cobalt and iron ions of the glaze were determined by X-ray absorption spectroscopy (XAS), particularly X-ray absorption near edge structure (XANES), using synchrotron radiation. Spectral features demonstrated that both cobalt and iron speciation were affected by the firing atmosphere and therefore could be used to ascertain the firing atmosphere.